Wind energy and assessment of wind energy potential in Turkey - Ilkilic, Cumali (Pergamon-Elsevier Science Ltd, 2012)
In this study, the potential of wind energy and assessment of wind energy systems in Turkey were studied. The main purpose of this study is to investigate the wind energy potential and future wind conversion systems project in Turkey. The wind energy potential of various regions was investigated; and the exploitation of the wind energy in Turkey was discussed. Various regions were analyzed taking into account the wind data measured as hourly time series in the windy locations. The wind data used in this study were taken from Electrical Power Resources Survey and Development Administration (EIEI) for the year 2010. This paper reviews the assessment of wind energy in Turkey as of the end of May 2010 including wind energy applications. Turkey's total theoretically available potential for wind power is around 131,756.40 MW and sea wind power 17,393.20 MW annually, according to TUREB (TWEA). When Turkey has 1.5 MW nominal installed wind energy capacity in 1998, then this capacity has increased to 1522.20 MW in 2010. Wind power plant with a total capacity of 1522.20 MW will be commissioned 2166.65 MW in December 2011. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Wind energy; Wind power; Renewable energy; Wind plants